Biomechanical tests and finite element analyses of pelvic stability using bilateral single iliac screws with different channels in lumbo-iliac fixation - Sun, Yangyang; Fu, Ying; Liu, Fanxiao; Zhang, Wen; Ma, Huanzhi; Li, Qinghu; Zhou, Dongsheng; Fu, Baisheng (Frontiers in Surgery, 2022)
Background: In lumbo-iliac fixation, the iliac screw can be placed in several locations and directions. There is no uniform standard for the placement of a single iliac screw. Biomechanical tests and finite element analyses were used to compare the effect of bilateral single iliac screws with three channels on pelvic stability to determine the best channel. Methods: Five embalmed adult cadaver pelvic specimens were selected. An unstable Tile C1 pelvic injury model was established. Lumbo-iliac fixation for the treatment of left sacral Denis II fracture includes the following: three channels of bilateral, single iliac screws (channel A from posterior superior iliac spine (PSIS) to anterior inferior iliac spine (AIIS), channel B from 1 cm medial and 1 cm caudal of PSIS to AIIS, and channel C from 2 cm below PSIS to AIIS). Biomechanical testing was performed for stiffness evaluations. A finite element model was established to study the stress distribution of the model and the maximum von Mises stress of internal fixation. Results: Biomechanical tests revealed that under vertical compression loading. The compressive stiffness fixed by channel B (246.15 ± 27.85 N/mm) was better than that fixed by channel A and channel C. Under torsional load, the torsional stiffness fixed by channel B (2.234 ± 0.223 N · m/°) was stronger than that fixed by channel A and channel C. However, there was no significant difference in terms of compressive and torsional stiffness between channel B and channel A (P > 0.05). Finite element analyses conformed that the maximum von Mises stress of the internal fixator fixed in channel B under the conditions of vertical, forwards bending, backwards extension, left bending, left rotating, and right bending (213.98 MPa, 338.96 MPa, 100.63 MPa, 297.06 MPa, 200.95 MPa and 284.75 MPa, respectively) was significantly lower than those fixed in channel A and channel C. Conclusions: The construct stiffness of the channel from 1 cm medial and 1 cm caudal of PSIS to AIIS is better than that of the other two channels. This channel has the advantages of good biomechanical stability, small maximum von Mises stress of internal fixation.